Association of toll-like receptors polymorphisms with COPD risk in Chinese population - Sun, Shulei; Shen, Yuehao; Feng, Jing (Frontiers in Genetics, 2022)
Background: Previous studies have reported that the Toll-like receptors (TLRs) are related with the progress of chronic obstructive pulmonary disease (COPD). We aimed to explore the association of TLRs single nucleotide polymorphisms (SNPs) and COPD risk. Methods: 170 COPD patients and 181 healthy controls were enrolled in this case-control study. MassARRAY platform was used for genotyping seven tagging SNPs (TLR2: rs3804100, rs4696480, rs3804099; TLR3: rs3775290, rs3775291, rs5743305; TLR9: rs352140) of TLRs. The correlations between the SNPs and COPD risk were determined using logistic regression. Results: We found that the rs3775291 of TLR3 significant decreased the risk of COPD (TT versus CC: non-adjusted OR = 0.329, 95% CI = 0.123–0.879, p = 0.027). In the genetic models analysis, the rs3775291 was associated with a decreased effect of COPD based on the recessive model (TT versus CC/CT: non-adjusted OR = 0.377, 95% CI = 0.144–0.988 p = 0.047). The rs4696480 of TLR2 gene was associated with a decreased risk of COPD after adjustment by age and gender (TA versus AA: adjusted OR = 0.606, 95% CI = 0.376–0.975, p = 0.039). Conclusion: Our study showed that genetic variants in TLRs were associated with risk of COPD. The rs3775291 and rs4696480 may act as a potential biomarker for predicting the risk of COPD in Chinese population.